HelloTalk’s Role in Enhancing English Speaking Skills: A Lesson from Technology-Assisted Language Learning - Meliana, Meliana; Yananda, Yeni; Hasanah, Syafaatul; Ariawan, Soni; Khusniyah, Nurul Lailatul (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
The use of technologies in language learning can improve EFL students’ learning outcomes. One of them is HelloTalk application. It has great potential to be a useful language learning tool. This is reinforced by the results of another study which found that interacting directly with native speakers is essential for improving language skills. Therefore, this study investigates the effectiveness of the HelloTalk application in improving English-speaking skills among fifth-semester students at State Islamic University of Mataram. Using a qualitative research approach, data were collected through observations and semi-structured interviews to explore students' experiences and progress in vocabulary acquisition, pronunciation accuracy, and fluency development. The findings indicate that HelloTalk significantly enhances students' lexical range, as frequent exposure to real-time conversations expands their vocabulary. Moreover, students reported improvements in pronunciation, particularly in distinguishing challenging phonemes, due to instant feedback from native speakers. Additionally, fluency increased as students became more confident in engaging in spontaneous dialogue with fewer pauses. However, several challenges were identified, including the high cost of premium features, internet connectivity issues, and complex app functionalities that hindered some students, particularly beginners. Despite these limitations, HelloTalk proves to be an effective tool for technology-assisted language learning, supporting real-world conversational practice. The study suggests that integrating HelloTalk into formal language courses could maximize its benefits while addressing its limitations through institutional support.